Ge-Doped bismuth vanadate solid electrolytes: synthesis, phase diagram and electrical properties - Lee, Chnoong Kheng; Tan, Meow Peng; West, Anthony R. (Royal Society of Chemistry (RSC), 1994)
The location of Ge-doped Bi4V2O11 solid solutions in the Bi2O3-V2O5-GeO 2 ternary phase diagram has been determined; a more detailed study of the Bi4V2O11-Bi2GeO5 join has been carried out and the phase diagram presented. The main mechanisms for solid solution formation appear to involve substitution of both Ge and Bi into V sites, giving rise to the general formula Bi4+yV 2-2x-yGe2xO11-x-y: -0.04<y<0.23; 0<x<0.45 (not all values of x and y in these ranges). Conductivity of the α and γ polymorphs both on and off the Bi4V 2O11-Bi2GeO5 join generally decreases with increasing x after an initial increase. In addition, conductivity of the γ polymorph decreases with increasing Bi2O3 content, y; the highest conductivity was obtained at x = 0.305 and y = 0.07.